Implementation of Business Ethics For Muslim Traders in Digital Business Competition - Mahrudin, Lintang Fajar; Wibisono, Anton (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2024)
This study aims to analyze the application of business ethics among Muslim traders in facing competition in digital business. In the digital economy era, business activities have increasingly evolved by utilizing technology as the primary medium for transactions. Therefore, it is essential to examine digital business practices from the perspective of Islamic business ethics to ensure that economic activities remain aligned with Sharia principles. This research employs a descriptive qualitative method with a literature review approach. The data utilized in this study are derived from various scholarly discussions on Islamic business ethics and the current developments in digital business. The findings indicate that business practices within the digital economy generally fall under the domain of muamalah, which is permissible unless explicitly prohibited by religious texts. In digital business practices, prudence and honesty serve as fundamental principles that Muslim traders must uphold. Additionally, other principles of Islamic business ethics, such as justice, transparency, and social responsibility, must also be implemented to ensure sustainable and ethically sound business operations in accordance with Islamic values. The implications of this study highlight that while the digital economy provides vast opportunities for business actors, it also increases the risk of ethical violations. Therefore, the application of Islamic business ethics is crucial to maintaining integrity and ethical compliance in digital business. This research contributes to a deeper understanding of the significance of business ethics in the digital economy and how Islamic principles can be effectively applied in an increasingly competitive business environment.